2021 Handbook of Florida Water Regulation: Agricultural Best Management Practices - Michael T. Olexa; Tatiana Borisova; Jana Caracciolo (EDIS)
This handbook is designed to provide a summary of the principal federal and state (Florida) laws that directly or indirectly relate to agriculture. Because these laws are subject to constant revision, portions of the handbook could become outdated at any time. The reader should use it as a means to determine areas in which to seek more information and as a brief directory of agencies that can help answer more specific questions.